PERLINDUNGAN HUKUM ATAS HAK KENYAMANAN KONSUMEN BAGI PENYANDANG DISABILITAS DI DALAM STASIUN KERETA API COMMUTER LINE - Nisa Nurphita Ritonga; Jeane Neltje (Fakultas Hukum Universitas Tarumanagara, 2021)
Nowadays, the need for comfortable transportation is increasingly needed by people including people with disabilities in commuter line transportation. But in practice there are still inconveniences in using the Commuter Line train. How the legal protection of the consumer's right to comfort as a user of the Exclusive Train Commuter Transport train is an issue discussed. The research method used is normative descriptive research method based on secondary data and primary data as qualitatively analyzed supporting data. The results illustrate that PT KCI has not provided legal protection for people with disabilities users of commuter rail services linesebaga imana stipulated in Article 3 UUKA and Article 4 Paragraph (1) UUPK, The inconvenience is caused by the infriendly facilities in the train station for passengers as consumers with disabilities and cause one of the passengers with disabilities mired from the platform to touch the railway track